Introduction: Mestizo acts. Issue 3 (1st September 2016) - Eiss, Paul K.
ABSTRACT: How is one to approach mestizaje in a way that is not definitionally predicated on 'race, ' or at least, on a modernist formulation of race as phenotypically expressed biological difference? The contributors to this volume provide explorations of this question in varied national contexts (Mexico, Guatemala, Bolivia, Colombia, Peru), from the16th century to the present. They treat 'mestizo acts' neither as expressions of preexisting social identities, nor as ideologies enforced from above, but as cultural performances enacted in the in-between spaces of social and political life. Moreover, they show how 'mestizo acts' not only express or reinforce social hierarchies, but institute or change them – seeking to prove – or to dismantle – genealogies of race, blood, sex, and language in public and political ways.